Editor's Note = Note du directeur [36, Fall 1995] - Kealey, Gregory S. (Labour / Le Travail, 1995)
Announces the launch of the Canadian Committee on Labour History's website and Michael Lonardo's Canadian labour history bibliography (English only), with the latter on the website of Memorial University. Sean Cadigan has joined the editorial team as assistant editor and Andrew Parnaby is doing an internship as did his predecessor Michael Butt. Donations were also received to establish the Eugene Forsey Prize for student essays on labour and working-class history and to continue the work on labour education.
Keywords: CADIGAN; Sean; Canada; PERIODICAL editors; PERIODICALS; WEBSITES; WORLD Wide Web